Réserve de Biosphère de Yangambi à l’épreuve de la cristallisation des pratiques locales de survie : une réponse à la faillite de l’État en République Démocratique du Congo - Justin Kyale Koy; Alphonse Maindo Monga Ngonga; David Andrew Wardell (VertigO, 2019)
The issue of local practices to survive developed by local communities living around protected areas in the Democratic Republic of Congo is based on two different logics that are irreconcilable. In the first case, the country is pursuing a nature conservation policy without ensuring a minimum of attention for local development. In the second case, the lack of alternative economic activities to survive leads local communities to have to exploit natural resources. This study analyses the survival activities of local communities living around the Man and the Biosphere Reserve of Yangambi, as a response to the failure of the State. The analysis is based on the triangulation of data sources from focus group discussions, historical archives and semi-structured interviews. The investigations reveal a wide range of activities including agriculture, fishing, hunting, mining, forestry and the exploitation of other non-timber forest products. The gains of local community development initiatives from the late colonial Belgian Congo period were not consolidated by the postcolonial State which abandoned them due to its own failures. The direct or indirect involvement of public authorities in these activities makes enforcement difficult.